Spiritual Homelands : The Cultural Experience of Exile, Place and Displacement among Jews and Others - Biemann, Asher D.; Cohen, Richard I.; Wobick-Segev, Sarah E. (Perspectives on Jewish Texts and Contexts ;, 2019)
Homeland, Exile, Imagined Homelands are features of the modern experience and relate to the cultural and historical dilemmas of loss, nostalgia, utopia, travel, longing, and are central for Jews and others. This book is an exploration into a world of boundary crossings and of desired places and alternate identities, into a world of adopted kin and invented allegiances.